Influence of Marble Powder and Polypropylene Fibers on the Strength and Durability Properties of Self-Compacting Concrete (SCC). (30th September 2022) - Ali, Atizaz; Hussain, Zahoor; Akbar, Muhammad; Elahi, Ayub; Bhatti, Samiullah; Imran, Muhammad; Zhang, Pu; Leslie Ndam, Nembo
Abstract : The purpose of this study was to investigate the effect of polypropylene fiber reinforced self-compacting concrete (SCC) at both the fresh and hardened stages, as well as their durability behavior. Properties of marble powder-based fiber reinforced SCC at fresh state were studied by means of slump flow diameter and flow time, V-funnel, and L-box test. The concrete properties at the hardened state were examined regarding compressive strength, split tensile strength, and flexural strength. Cement was replaced with marble powder with a substituting ratio of 4%, 8%, 12%, and 16% while polypropylene fibers were added as 0.1%, 0.2%, 0.3%, and 0.4%. The durability properties were analysed in the form of water permeability and chloride migration. In accordance with the outcomes of the tests, the workability of SCC deteriorated with an increase in fiber content, although it performed effectively at higher marble dosages. There was little impact of fibers on compressive strength and water permeability property of SCC. However, by adding the fibers in SCC improved both the split tensile strength and flexural strength by 16.92% and 11.36%, respectively. The addition of marble powder showed a synergetic effect with polypropylene fibers, which showed its applicability in SCC. The chloride resistance was improved at lower content of polypropylene fiber addition. For optimizing polypropylene fibers (pp) and marble powder substitution, the polynomial work expectation justifies the response surface technique (RSM). When a p value of 0.05 is used to analyse the variation in the (Linear-ANOVA), the model is considered statistically significant. Performance of concrete was greatly enhanced by substituting 12% marble powder with cement and adding 3% polypropylene fiber.